Динамика электромашинных следящих систем - Блейз Е. С. Евгений Семенович; Семенов Ю. Н. Юрий Николаевич; Чемоданов Б. К. Борис Константинович; Якименко Н. М. Николай Маркович (Москва, Энергия, 1967)
Исключено из фонда НТБ ТПУ